ERBB2 expression as potential risk-stratification for early cystectomy in patients with pT1 bladder cancer and concomitant carcinoma in situ - Breyer, Johannes; Erben, Philipp; Kriegmair, Maximilian (Urologia internationalis, 2017)
Background/Aims/Objectives: It is difficult to identify patients with a non-muscle-invasive bladder cancer (NMIBC) at stage pT1 with concomitant carcinoma in situ (Cis) who will benefit from an early cystectomy. Methods: We retrospectively analyzed clinical data and formalin-fixed paraffin-embedded tissues of patients with NMIBC. Messenger ribonucleic acid (mRNA) expression of progesterone receptor (PGR), estrogen receptor (ESR1), ERBB2, and marker of proliferation Ki-67 (MKI67) was measured by single-step reverse transcription quantitative real-time polymerase chain reaction using RNA-specific TaqMan assays. Relative gene expression was determined by the normalization of 2 reference genes (CALM2, B2M) using the 40 ΔΔCT method and relative gene expression was correlated to the histopathological stage and oncological outcome. Results: Of 302 patients with pT1 NMIBC in the initial transurethral resection of the bladder, 65 had a concomitant Cis. Elevated ERBB2 expression (>40.1) significantly correlated with progress in patients with and without concomitant Cis (p = 0.020 and p = 0.049, respectively). For the subgroup of pT1 with concomitant Cis, elevated ERBB2 expression significantly discriminated between a high-risk group of 55% progression-free survival (PFS) and a low-risk group of 90% PFS after a 5-year follow-up (p = 0.020). Cox-regression analysis revealed ERBB2 expression as the only independent prognostic factor for PFS (p = 0.0037). Conclusions: High mRNA expression of ERBB2 can identify patients with pT1 NMIBC with concomitant Cis, who have a high risk of progression and might benefit from an early cystectomy.